Mutations in the NOT Genes or in the Translation Machinery Similarly Display Increased Resistance to Histidine Starvation - Collart, Martine A.; Kassem, Sari; Villanyi, Zoltan (Frontiers in Genetics, 2017)
The NOT genes encode subunits of the conserved Ccr4-Not complex, a global regulator of gene expression and in particular of mRNA metabolism. They were originally identified in a selection for increased resistance to histidine starvation in the yeast S.cerevisiae. Recent work indicated that the Not5 subunit, ortholog of mammalian CNOT3, determines global translation levels by defining binding of the Ccr4-Not scaffold protein Not1 to ribosomal mRNAs during transcription. This is needed for optimal translation of ribosomal proteins. In this work we searched for mutations in budding yeast that were resistant to histidine starvation using the same selection that originally led to the isolation of the NOT genes. We thereby isolated mutations in ribosome-related genes. This common phenotype of ribosome mutants and not mutants is in good agreement with the positive role of the Not proteins for translation. In this regard, it is interesting that frequent mutations in RPL5 and RPL10 or in CNOT3 have been observed to accumulate in adult T-cell acute lymphoblastic leukemia (T-ALL). This suggests that in metazoans a common function implicating ribosome subunits and CNOT3 plays a role in the development of cancer. In this perspective we suggest that the Ccr4-Not complex, according to translation levels and fidelity, could itself be involved in the regulation of amino acid biosynthesis levels. We discuss how this could explain why mutations have been identified in many cancers.